Cognitive behavioral therapy informed workshop on sleep: a preliminary randomized controlled trial - Chu, Michelle Hiew Mun; Chan, Joanna Eileen; Sanjeetra, Ravindharan (2022)
The aim of this study is to evaluate the effectiveness of CBT-informed workshop on sleep: A preliminary randomized controlled trial in improving sleep quality and life quality among undergraduate students in Malaysia. One of the challenges faced by university students is not having sufficient sleep and it may affect the quality of life. In this randomized controlled trial, participants were randomly allocated to intervention group (n = 15) and control group (n = 13). The results showed that there is significant improvement (p = .038) in their sleep quality in the post-workshop when compared to the pre-workshop, with the effect size (η2) is = .358. For quality of life, physical health (p = .056) and social relations (p = .032) showed a significant results in this study. Findings supports the effectiveness of CBT-informed workshop on sleep among undergraduates and can be implemented as an effective health-care programme to improve sleep quality and quality of life through clinical and psychological practice.